Sustainable development of Iran's medicinal plant exports to the global value chain: a strategic analysis - Shariatzadeh, Maryam; Bijani, Masoud; Bahadori, Farzane (Frontiers in Sustainable Food Systems, 2025)
IntroductionIran, with a wide variety of climates, is among the top 20 countries in the world in terms of medicinal plant production, yet it does not have a significant position among the top exporting countries of medicinal plants and related products. Therefore, this exploratory descriptive research was conducted with the aim of analyzing the strategic development for sustainable export of medicinal plants from Iran to the global value chain using the SWOT technique.MethodsThe study population consisted of three groups: experts in medicinal plants, managers and relevant experts in agricultural administrations, natural resources and watershed management, Agriculture and natural resources research and education center, as well as producers, traders, and managers in the field of medicinal plants, with 31 individuals selected purposefully as a sample using snowball sampling method.Results and discussionBased on the findings, 10 strengths, 25 weaknesses, 11 opportunities, and 16 threats were identified. The results indicated that the average weaknesses outweighed the strengths, and threats outweighed the opportunities. Therefore, the strategic quadrant of the SWOT matrix was placed on the WT (defensive strategies). Accordingly, some proposed strategies such as “Encouraging regional investment in the field of medicinal plant processing industries” and “Reforming and facilitating administrative bureaucracy to obtain necessary licenses for final product production” were suggested to play a more significant role in the development of medicinal plant production and processing. The findings of this study can be utilized by decision-makers and relevant policymakers in planning and for sustainable development of Iranian medicinal plant exports in the global value chain.